Duplication of R&D and industry concentration - Temimi, Akram (2001)
The purpose of the literature on Research Joint Ventures (RJV), pioneered by DíAspremont and Jacquemin (1988) and Kamien, Muller, and Zang (1992), has been to combine the best of two worlds: to appropriately deal with R&D spillovers while preserving competition in the product market. Moreover, RJVs eliminate duplication of R&D. Thus, at least in theory, RJVs dominate other solutions such as subsidies. If, however, we are concerned about risks of cartelization, then Spenceís (1984) subsidy-based solution for independently acting firms, is a viable alternative that cannot be dismissed. Indeed, in contrast to the previous literature, we find that in the presence of R&D subsidies, market performance may unambiguously improve with the number of firms in the market.